Research on the Age of Coal-bearing Strata in Beishan basin group of Gansu-Inner Mongolia Region. Issue 5 (February 2020) - Niu, Haiqing; Han, Xiaofeng; Cui, Haifeng
Abstract: Although the coal measures strata of Beishan Basin group in Ganmeng were discovered earlier, due to the low degree of geological work and the lack of comprehensive data system research, the geogical age of coal measures strata is not consistent. In order to clarify the age of coal measures strata in the basin group and the exploration prospect of coal, uranium, oil and other resources in the research area, the geological age of coal measures strata in Beishan basin group was Researched, based on the systematic summary of paleontology, tectonic evolution, lithologic characteristics and coal and rock industrial characteristics, combined with the analytical and laboratory data supplemented by the research team, the comprehensive analysis shows that: the age of the formation of the coal measures in Beishan basin group should be the early cretaceous of the Middle Jurassic.The geogical age of the coal measures in southern of the basin group is the Jurassic, and the northern coal measures are mainly early cretaceous.The western margin of Yinhe basin is adjacent to Beishan basin group, and the coal measures strata are comparable to each other, which can provide the basis for the age of coal measures strata revealed by drilling holes in the western margin of Yinhe basin.